Mechatronics 2017 - Ideas for Industrial Applications - Świder, Jerzy; Kciuk, Sławomir; Trojnacki, Maciej (Advances in Intelligent Systems and Computing,, 2019)
This book is devoted to the latest research results obtained by scientists and practitioners, who work on the development and applications of mechatronics, in particular in industrial practice. The topics included in the book cover such areas and issues as: measurement techniques in phenomena and mechatronic problems, robotics and design of mechatronic systems, research and application of mechatronics in medicine and sports, modern applications of mechatronics in rapidly changing modern mining, which puts strict demands on safety of people and the environment, application of mechatronics in the automotive industry in the design and production process of modern cars, defense technologies, extremely demanding aerospace industry, contemporary food industry, as well as didactics of mechatronics lead at different universities in the paradigm of Industry 4.0.